2008
DOI: 10.3860/taper.v17i1.347
|View full text |Cite
|
Sign up to set email alerts
|

Practicing Entrepreneurship Education for Secondary Pupils through the Operation of a New Year Stall in Hong Kong

Abstract: The existing business curriculum in Hong Kong secondary schools lacks significant programs in entrepreneurship education. This paper will look at the effect of the implementation of an entrepreneurial activity, the running of a New Year stall, on pupils. This research will look at three schools of different bandings which participated in the running of New Year stalls. Both teachers and pupils of the three schools taking part in the activity were recruited. In-depth interviews were conducted with teachers and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 18 publications
0
16
0
1
Order By: Relevance
“…Curriculum. The subjects of study were mostly on curricula (Bakar et al, 2001;Cheung, 2008;Hamid, 2013;Seikkula-Leino, 2011). The curricula concerned here were basic education curricula (Hamid, 2013;Kleppe, 2002;Orji, 2014); for example, coverage of entrepreneurship education in primary and/or middle school curricula (Hamid, 2013;Orji, 2014), lack of entrepreneurship education study at primary school level (Kleppe, 2002), inadequacy of the high school curriculum in terms of entrepreneurship education (Cheung, 2008), and the necessity of expanding entrepreneurship in general education and vocational education (Caseiro & Alberto, 2013).…”
Section: The Distribution Of the Studies In Terms Of Needsmentioning
confidence: 99%
See 1 more Smart Citation
“…Curriculum. The subjects of study were mostly on curricula (Bakar et al, 2001;Cheung, 2008;Hamid, 2013;Seikkula-Leino, 2011). The curricula concerned here were basic education curricula (Hamid, 2013;Kleppe, 2002;Orji, 2014); for example, coverage of entrepreneurship education in primary and/or middle school curricula (Hamid, 2013;Orji, 2014), lack of entrepreneurship education study at primary school level (Kleppe, 2002), inadequacy of the high school curriculum in terms of entrepreneurship education (Cheung, 2008), and the necessity of expanding entrepreneurship in general education and vocational education (Caseiro & Alberto, 2013).…”
Section: The Distribution Of the Studies In Terms Of Needsmentioning
confidence: 99%
“…This theme was followed by the consideration of aims about entrepreneurial activities that were designed, used and evaluated within the scope of entrepreneurship education (Hannula et al, 2012;Hietanen, 2013;Oplatka, 2014;Ruskovaara, Pihkala, Seikkula-Leino, & Järvinen, 2015). For example, investigating the influences of entrepreneurial activities on teachers and students (Cheung, 2008), examining the ways entrepreneurship is taught in different middle schools (Brown, 2012), examining the entrepreneurial activities created by teachers (Oplatka, 2014), and showing practices that have a potential to encourage creativity, innovativeness and entrepreneurship (Cankar, Deutsch, Zupan, & Cankar, 2013).…”
Section: The Distribution Of the Studies In Terms Of Aimsmentioning
confidence: 99%
“…Involving the younger population of a country (i.e., students) in CSR program has an advantage because it can act as an eye-opener to the students in terms of reality in future employment options (Keitel 2008;Cheung 2008). Students gain the required employability skills, such as teamwork, not only through the structured curriculum but also through students' exposure to the companies.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Several researchers have evaluated the impact of EE on individuals' entrepreneurial intentions through attitudes (e.g., Carayannis et al, 2003;Shinnar et al, 2009;Lourenço et al, 2013;Fayolle et al, 2014;Fellnhofer and Kraus, 2015). Several studies discovered that EE can have a positive impact on entrepreneurial attitudes by increasing the perceived attractiveness of entrepreneurship (e.g., Dickson, 2004;Krueger, 2007;Cheung, 2008;Petridou and Glaveli, 2008;Von Graevenitz et al, 2010). Further, researchers have shown that attitudes influence behaviours and behaviours influence attitudes (Brännback et al, 2007;Fretschner and Weber, 2013).…”
Section: Eight Impact Variables As Indicators For An Adequate Educatimentioning
confidence: 99%